2016
DOI: 10.1155/2016/5127374
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of an Active Rehabilitation Intervention in a Slow-to-Recover Paediatric Population following Mild Traumatic Brain Injury: A Pilot Study

Abstract: Objective. The aim of this study was to identify whether the addition of an individualised Active Rehabilitation Intervention to standard care influences recovery of young patients who are slow-to-recover following a mTBI. Methods. Fifteen participants aged 15 ± 2 years received standard care and an individualised Active Rehabilitation Intervention which included (1) low- to high-intensity aerobic training; (2) sport-specific coordination exercises; and (3) therapeutic balance exercises. The following criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…Active rehabilitation interventions commonly consist of aerobic exercise, alongside coordination drills, visualization, and education. Several studies on active rehabilitation interventions for youth with persistent symptoms have found improvement in symptoms following intervention (see for example Dobney et al, 2017;Gagnon et al, 2009Gagnon et al, , 2015Imhoff et al, 2016;Kurowski et al, 2017;Lawrence et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Active rehabilitation interventions commonly consist of aerobic exercise, alongside coordination drills, visualization, and education. Several studies on active rehabilitation interventions for youth with persistent symptoms have found improvement in symptoms following intervention (see for example Dobney et al, 2017;Gagnon et al, 2009Gagnon et al, , 2015Imhoff et al, 2016;Kurowski et al, 2017;Lawrence et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A review of guidelines for concussion care emphasizes the effectiveness of patient/family education specifically to validate symptoms, outline the expected trajectory of recovery, and help establish realistic goals [1] [26] [27] [28] [29]. Guidelines for concussion care also highlight symptom management and the importance of establishing techniques to stay within a subthreshold level so as not to exacerbate the symptoms [30] [31].…”
Section: Introductionmentioning
confidence: 99%
“…[20] [26] [27] [28] [29] [30] [41]. The more understanding patients have regarding their symptoms, the less likely they are to overreact to them or attribute them to significant brain damage[6] [42] [43].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, adolescents who engaged in a rehabilitation program involving physical activity within the first month after concussion experienced reduced symptoms (Chrisman et al, 2017;Grool et al, 2016). Additionally, rehabilitation programs that included structured aerobic physical activity for adolescents with persistent symptoms beyond one-month reduced persistent symptoms (Gagnon, Galli, Friedman, Grilli, & Iverson, 2009;Gagnon, Grilli, Friedman, & Iverson, 2016;Imhoff, Fait, Carrier-Toutant, & Boulard, 2016;Kurowski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%